Immune Profiling of Cord Blood From Preterm and Term Infants Reveals Distinct Differences in Pro-Inflammatory Responses - Anderson, Jeremy; Thang, Cao Minh; Thanh, Le Quang; Dai, Vo Thi Trang; Phan, Van Thanh; Nhu, Bui Thi Hong; Trang, Do Ngoc Xuan; Trinh, Phan Thi Phuong; Nguyen, Thuong Vu; Toan, Nguyen Trong; Harpur, Christopher M.; Mulholland, Kim; et al. (Frontiers in Immunology, 2021)
Abstract Background Preterm infants are highly vulnerable to infectious disease. While many factors are likely to contribute to this enhanced susceptibility, the immature nature of the preterm immune system is postulated as one key factor. Methods In our study, we used high-dimensional flow cytometry and cytokine assays to characterise the immune profiles in 25 preterm and 25 term infant cord blood samples. Results We found that preterm infants exhibit reduced frequencies of monocytes, CD56bright NK cells, CD8+ T-cells, γδ T-cells and an increased frequency of intermediate monocytes, CD4+ T-cells, central memory CD4+ and CD8+ T-cells, Tregs and transitional B-cells compared to term infants. Pro-inflammatory cytokines IL-1β, IL-6 and IL-17A were lower in preterm infants in addition to chemokines IL-8, eotaxin, MIP-1α and MIP-1β. However, IL-15 and MCP-1 were higher in preterm infants. Conclusion Overall, we identify key differences in pro-inflammatory immune profiles between preterm and term infants. These findings may help to explain why preterm infants are more susceptible to infectious disease during early life and facilitate the development of targeted interventions to protect this highly vulnerable group.